Philosophical Thoughts in Brahmanism and its Impacts on Cham People in Vietnam - Trinh, Trang (Kalágatos, 2023)
Philosophical thought in Brahmanism has had a great impact on the life, religion and culture of the Indian region in general and the Cham people in Vietnam in particular. This thought introduces concepts such as Brahman, reincarnation, connection and self-awareness, providing a holistic view of the world and one’s place in it. Brahmanism has shaped religions such as Hinduism and influenced the development of Buddhism and Islam in the region. Although it has undergone change and challenge, this ideology is still present in the religions and cultures of the region, with deep cultural and philosophical values. In Vietnam, the Cham people are one of 54 ethnic groups living in the same territory. The Cham people have received Brahmanism and modified it to suit the living conditions of people. The process of introducing Brahmanism, along with concepts such as Brahman, reincarnation and the interconnection of all things, Brahmanism has created a profound way of looking at the world and life. This ideology has influenced the culture, religion and spiritual life of the Cham people. However, with the exposure and impact of other religions such as Buddhism and Islam, Brahmanism thought has become less popular in the Cham community. In this article, from the perspective of philosophy, the author will clarify the ideas of philosophy in Brahmanism and its impact on the Cham people in Vietnam.